ANTIOXIDANT ACTIVITY ASSAY ETANOL EXTRACT OF PEPAYA LEAVES (Carica Papaya L.) FROM ACEH BESAR - Tafonao, Joni Alman; Tammi, Isral; Damay, Rizki Damayanti; Zulfajri, Muhammad; Sembiring, Desi Sri Pasca Sari; Zai, Liver Iman Putra (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2024)
The leaves, fruits, and roots of papaya (Carica papaya L) are mostly used as traditional medicine. Papaya leaves are used by the community to treat diarrhoea, acne, appetite, and digestive problems. Papaya leaf extract has potential as an antioxidant derived from secondary metabolites, namely alkaloid compounds that produce a bitter taste in papaya leaves. This study was conducted to look at antioxidant compounds by conducting antioxidant activity tests. The results of papaya leaf research contain active compounds flavonoids, alkaloids, and steroids. Research conducted on the level of colour brightness in papaya leaves is different, namely 10 ppm, 25 ppm, 50 ppm, 75 ppm and 100 ppm. Papaya leaf extract has a power that is included in the strong category with the IC50 value obtained 8.71 marked by the results of calculations less than 100. Antioxidant activity testing using the DPPH method papaya leaf extract positively contains antioxidant compounds and can be utilised as a natural antioxidant.